One Year After the 2011 Triennial Surveillance Review : Progress Report. (Policy Papers; Policy Paper ;, 2012)
This progress report provides a short update on the first year of implementation of the 2011 Triennial Surveillance Review (TSR) in line with the Managing Director's Statement on Strengthening Surveillance of October 2011. The report does not provide a comprehensive review of surveillance-which will be done in the 2014 TSR. Instead, its purpose is to establish, at an early stage, whether the new operational priorities are being implemented, set out key areas of progress, and discuss the challenges raised in their implementation. The report also identifies areas where further efforts may need to be directed-particularly following the change to the legal framework-to ensure even implementation and delivery of effective surveillance. The report recognizes that, while some measures have been implemented over the past year, others will take more time to come to fruition.